Pathogenicity of Isaria fumosorosea to European red mite in the laboratory - Cláudia Andréia Gräff; Liana Johann; Cláucia Fernanda Volken de Souza; Noeli Juarez Ferla (Biotemas)
Vineyard in Rio Grande do Sul State, Brazil have suffered significant infestations of mites, especially Panonychus ulmi (Koch) recently. There are reports on the ability to control mites with Isaria fumosorosea. The objective of this study was to evaluate in the laboratory the pathogenicity of I. fumosorosea to P. ulmi mites. Panonychus ulmi was reared from harvests from vineyards in Serra Gaucha. Fungal spore suspensions at different concentrations were applied to P. ulmi eggs. Triplicates of females, 12 to 15 days old, were treated with a spore suspension of 108 mL-1. Controls were treated with distilled water. Seven days after application, 55.6% of eggs treated with a spore suspension of 106 mL-1 did not hatch, and treated females showed a total mortality of 85-90% and confirmed mortality of 50-55%. The maximum mortality of water-treated control eggs and females was on average 12.8 and 15.5%, respectively. It is concluded that the I. fumosorosea isolate has the ability to infect eggs and adult females of P. ulmi and thus appears to be a viable alternative to be tested in the field.